Tanggung Jawab Pemegang Kekuasaan Negara Dalam Menjamin Hak Warga Negaranya Atas Udara Bersih Dan Sehat - Winaldy, Rickson; Andreyn, Sheilla Virginia; Nethan, Nethan (Jurnal Ilmiah Wahana Pendidikan, 2024)
The right to clean and healthy air is the basic right of every individual to live in an environment that does not pollute their health and maintains adequate air quality. The government has a leading role in regulating, monitoring, and protecting air quality through strict environmental regulations, strict law enforcement against violations, and the promotion of clean energy and sustainable transportation. International collaboration is needed to address the problem of transboundary air pollution, and careful monitoring of air quality is the basis for measuring progress and the effectiveness of actions taken. The impact of clean and healthy air is the country's solution to protect the welfare of society today and be sustainable for future generations. Human Rights are a set of rights that are inherent in the nature of humans as creatures of the Almighty God and are His gifts that must be respected, upheld and protected by the legal state, government and every person, for the sake of honor and protection of human dignity. A clean and healthy environment is a condition where all environmental elements, such as air, water, land and biodiversity, are free from pollution, contamination and damage that can endanger human health, ecosystem sustainability and ecological balance.